Perception of the coronavirus pandemic by patients with atopic dermatitis - Results from the TREATgermany registry - Helmert, Claudia; Siegels, Doreen; Haufe, Eva; Abraham, Susanne; Heratizadeh, Annice; Kleinheinz, Andreas; Harder, Inken; Schaekel, Knut; Effendy, Isaak; Wollenberg, Andreas; Sticherling, Michael; Stahl, Maren; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
Background TREATgermany, a registry for patients with moderate to severe atopic dermatitis (AD), established an additional questionnaire in spring 2020 to investigate the effects of the coronavirus pandemic on the daily life of patients with AD. Material and Methods A questionnaire was used to analyze general information regarding a patient's experience of the coronavirus pandemic and, using the Inventory of Life-Changing Events, the resulting personal burden. To analyze possible associations between disease severity (EASI score, oSCORAD, IGA, PGA, POEM), quality of life (DLQI) and personal burden, t-tests, analyses of variance and correlations were evaluated, controlled for sex and age. Results 58 % (n = 233) of the included 400 registry patients reported high burden scores caused by the coronavirus pandemic, regardless of an actual infection. Men showed significantly higher burden scores than women, and younger than older respondents (both P = 0.03). There were no differences in burden scores related to the physician's assessment of disease severity. However, patients with higher quality of life impairments and higher disease severity perceived the burden of the coronavirus pandemic as less severe (DLQI P = 0.019, PGA P = 0.044). Conclusions Our data show that registry patients considered the coronavirus pandemic as a life-changing event and perceived the burden differently. This should be taken into account in the treatment of patients with moderate to severe AD as well as in further studies.
CRIS-Team WoS Importer:2022-01-07